A comparative proteomic study of Homoharringtonine-induced apoptosis in leukemia K562 cells. Issue 7 (July 2015) - Zhou, Xuan; Xu, Na; Li, Rong; Xiao, Yajuan; Gao, Guanlun; Lu, Qisi; Ding, Li; Li, Ling; Li, Yuling; Du, Qingfeng; Liu, Xiaoli
Abstract The objective of this study was to determine the changes in protein profiles of K562 chronic myeloid leukemia (CML) cells in response to Homoharringtonine (HHT). HHT treatment significantly increased apoptosis of K562 cells. Proteomic analyses indicated 32 differentially expressed proteins, 13 of which were identified by mass spectrometry (nine down-regulated and four up-regulated). Aside from alterations in apoptotic proteins and proteins associated with transcription and translation, our data also revealed changes in oxidative stress response and redox reaction-related proteins, such as heat shock proteins (Hsps), DJ-1 and thioredoxin. Specifically, these proteins were validated to decrease after HHT treatment in K562 cells and in primary CML cells by immunoblot analysis. Additionally, Hsps, DJ-1 and thioredoxin, which were also shown to decrease in primary cells from imatinib-resistant patients, may be promising potential targets for mechanistic research and new clinical treatments.